SYSTEMIC ANTIBODY AND CELLULAR IMMUNE RESPONSES IN INFLUENZA INFECTION AND POSTSVACCINATION - S. A. Donina; A. N. Naikhin; G. D. Petukhova; I. B. Barantseva; T. V. Chirkova; Е. P. Grigor’eva; А. R. Rekstin; L. G. Rudenko (Медицинская иммунология, 2014)
Abstract. Post-infection immunity represents an immunogenicity standard for antiviral vaccines, including those against influenza. To estimate the immunogenic properties of vaccine preparations, it is necessary to compare the quantitative and qualitative parameters of immune responses to the vaccine strain and the virulent virus from which it is prepared. However, for ethical reasons, such human studies are difficult, because there is the possibility of pathogenic viral infection.The aim of this experimental work was to compare systemic immune responses to the pathogenic mouse influenza virus A (H1N1), and an attenuated reassortant virus, genetic formula 2/6 (R 2/6), an experimental analogue to the live influenza vaccine.It was shown, that R 2/6 lagged behind the pathogenic parental virus (PPV) in activated induction of circulating IgG-antibodies, secretion of a marker Th1-cytokine IFN-γ by splenocytes, and CTL (CD8+) production in the spleen. On the other hand, R 2/6 was highly competitive with PPV, with regard to quantitative proliferative parameters of pooled splenocytes, stimulation of Th (CD4+) cells, B-cells (CD19+), and Th2-cytokine IL-2. IL-6 production in the spleen was poorly induced by both viruses.Thus, attenuation of influenza A (H1N1) virus by the 2/6 genetic reassortment differentially influences the induction of systemic immunity constituents. i.e., some parameters of immune response may be reduced, while others are not altered. When preparing vaccine strains for live influenza vaccines, an attention should be given first of all to increased induction of circulating antibodies that comprise the major components of antiviral immunity.